The Motivation for Governance in the Establishment and Membership of Nonprofit Organizations (The International Journal for Scientific Research, 2025)
Nobility and virtue are often associated with charitable work. This research addresses the concept of positive selectivity, which must be contextualized within a framework of standards that govern all philanthropic processes, procedures, and outcomes—from the inception of the idea to the realization of results. The study highlights the issue of unregulated and undisciplined establishment of charitable organizations in the Kingdom of Saudi Arabia, as well as the challenges related to membership in such organizations and the consequential, often complex, problems that arise. The research proposes structured solutions aimed at achieving sound governance that instills integrity in the charitable sector, thereby preserving its noble and virtuous essence.
Keywords: Governance; Risk Management; Conflict of Interest; Nonprofit Organization; Motive; Intention; Stakeholders